Detection of mRNA expression patterns by nonradioactive in situ hybridization on histological sections of floral tissue - Medzihradszky, Anna; Schneitz, Kay; Lohmann, Jan U. (Flower Development, 2014)
Analysis of gene activity with high spatial resolution is a prerequisite for deciphering regulatory networks which underlie developmental programs. Over many years, in situ hybridization has become the gold standard for the identification of in vivo expression patterns of endogenous mRNAs. Nonetheless, the method has several limitations, and the detection of lowly expressed transcripts is still a challenge. Here, we present a robust protocol for sensitive analysis of expression patterns in inflorescence tissue of Arabidopsis thaliana. We describe how the samples are fixed, embedded, and sectioned in preparation for in situ hybridization, how RNA probes are prepared, and how hybridization and detection is carried out. While the described protocol is optimized for inflorescence meristems, it can possibly be used for other tissues as well.